(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aims to highlight the external influences that contributed to the enrichment of Arab Islamic culture through translation, which was one of the most important means of intellectual transmission among different peoples throughout the ages through the opening of the Abbasid state to the heritage of the former nations, whether the heritage of peoples under the control of the Abbasid state Neighboring peoples, such as the Greek, Indian and Chinese, became a general culture of society in which all social, economic, political and cultural groups participated. The impact and impact of Islamic civilization on other civilizations was clear, whether scientific, linguistic, economic and other influences. The study dealt with the factors of the emergence and prosperity of the translation movement in addition to the ways in which Muslims relied on translation and the centers that contributed to the reproduction of translators.The study also explained the efforts of the Abbasid caliphs in the translation process, with an emphasis on the efforts of the Caliph al-Ma’mun. Finally, the study showed the influence of civilizations in Islamic civilization represented in the renaissance of science and its prosperity, such as philosophy, mathematical sciences, astronomy, geography and medicine.